Sound-intensity feedback during running reduces loading rates and impact peak - Tate, J. J.; Milner, C. E. (Journal of Orthopaedic & Sports Physical Therapy, 2017)
Background: Gait retraining has been proposed as an effective intervention to reduce impact loading in runners at risk of stress fractures. Interventions that can be easily implemented in the clinic are needed. Objective: To assess the immediate effects of sound-intensity feedback related to impact during running on vertical impact peak, peak vertical instantaneous loading rate, and vertical average loading rate. Methods: Fourteen healthy, college-aged runners who ran at least 9.7 km/wk participated (4 male, 10 female; mean ± SD age, 23.7 ± 2.0 years; height, 1.67 ± 0.08 m; mass, 60.9 ± 8.7 kg). A decibel meter provided real-time sound-intensity feedback of treadmill running via an iPad application. Participants were asked to reduce the sound intensity of running while receiving continuous feedback for 15 minutes, while running at their self-selected preferred speed. Baseline and follow-up ground reaction force data were collected during overground running at participants' self-selected preferred running speed. Results: Dependent t tests indicated a statistically significant reduction in vertical impact peak (1.56 BW to 1.13 BW, P=.001), vertical instantaneous loading rate (95.48 BW/s to 62.79 BW/s, P = .001), and vertical average loading rate (69.09 BW/s to 43.91 BW/s, P=.001) after gait retraining, compared to baseline. Conclusion: The results of the current study support the use of sound-intensity feedback during treadmill running to immediately reduce loading rate and impact force. The transfer of within-session reductions in impact peak and loading rates to overground running was demonstrated. Decreases in loading were of comparable magnitude to those observed in other gait retraining methods.